Methylations in vitamin B12 biosynthesis and catalysis. (December 2022) - Mathur, Yamini; Hazra, Amrita B.
Abstract: Vitamin B12 is an essential biomolecule that assists in the catalysis of methyl transfer and radical-based reactions in cellular metabolism. The structure of B12 is characterized by a tetrapyrrolic corrin ring with a central cobalt ion coordinated with an upper ligand, and a lower ligand anchored via a nucleotide loop. Multiple methyl groups decorate B12, and their presence (or absence) have structural and functional consequences. In this minireview, we focus on the methyl groups that distinguish vitamin B12 from other tetrapyrrolic biomolecules and from its own naturally occurring analogues called cobamides. We draw information from recent advances in the field to understand the origins of these methyl groups and the enzymes that incorporate them, and discuss their biological significance. Highlights: The structures of vitamin B12 and other cobamides contain several methyl groups which confer distinct functions Pattern of methylations in the nucleotide loop and lower ligand contribute to the diversity of the cobamide cofactors. The recently discovered B12 -radical SAM superfamily enzymes are putting forth new mechanistic paradigms for B12 catalysis.